The Switch to Online Newspapers: Could Immediacy Be a Factor? - Omar, Bahiyah (2007)
Using remediation theory (Bolter and Grusin, 1999) as a guide, this study tested the concept of immediacy in a ‘between-subject’ design experiment that compared differential effects of exposure to print and online versions of The Australian newspaper. The results did not support the hypothesis that online readers would perceive greater immediacy than print readers. This seemed to contradict remediation’s view, yet the study did support the idea that immediacy is a factor in the switch of consumers from old to new media. Immediacy was strongly related to the goals of surveillance gratification seeking and moderately related to current issues knowledge. Because goals drive actions, this study suggests that immediacy could be responsible for the switch of customers to online newspapers as a consequence of its significant correlation to information seeking and knowledge acquisition.